Relevansi Model Bisnis dan Analisis SWOT Pariwisata Berbasis Masyarakat di Desa Pulisan - Porajow, Christine P.E; Erstiawan, Martinus Sony; Indriyanto, Machiko Nugraha (Jurnal Ilmiah Pariwisata, 2023)
This study aims to determine a business strategy by looking at the extent to which the community is prepared and involved in building a community-based tourism village with the integration of related parties in unraveling the potential for developing tourism objects with the Business Model Canvas (BMC) and SWOT analysis. Qualitative methods are used as a basis for developing real conditions based on informants, observations and documentation with the principle of triangulation as a basis for validity. The results achieved by the SWOT analysis refer to the rules/policies for the development of a sustainable phase where this strategy requires special attention and commitment from the community and local government. Availability of facilities and infrastructure, local community creativity (Human Resources) are needed in managing natural resources into tourism products in order to improve the regional economy. Knowledge, skills, organizational management, and utilization of information technology including websites and social media are identified as lacking values in the Pulisan community. Regarding the results, Canva's Business Model acts as a tool to decipher business strategies in preparing tourism village development plans based on village potential and SWOT identification to determine the focus of development patterns. Keywords: Business Model Canvas, Analisis SWOT, Tourist Villages